2023
DOI: 10.3390/polym15102291
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Recyclability of Additively Manufactured Polypropylene and Polylactic Acid Parts and Polypropylene Support Structures

Abstract: Polymers have a reputation for several advantageous characteristics like chemical resistance, weight reduction, and simple form-giving processes. The rise of additive manufacturing technologies such as Fused Filament Fabrication (FFF) has introduced an even more versatile production process that supported new product design and material concepts. This led to new investigations and innovations driven by the individualization of customized products. The other side of the coin contains an increasing resource and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Similarly, the elastic modulus of polypropylene decreases by 20% and the elastic modulus decreases by 12.9% with every recycling cycle [ 87 ]. The results corroborate those from Sun et al [ 75 ] and Nagengast et al [ 84 ] that the strength of polymers declines following exposure to UV light, leading to the shortening of the long-chain hydrocarbon bonds in the polymeric structure. Likewise, Gaikwad et al [ 77 ] acknowledged that recycled ABS has less than 90% of the strength of virgin ABS.…”
Section: Systematic Review and Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, the elastic modulus of polypropylene decreases by 20% and the elastic modulus decreases by 12.9% with every recycling cycle [ 87 ]. The results corroborate those from Sun et al [ 75 ] and Nagengast et al [ 84 ] that the strength of polymers declines following exposure to UV light, leading to the shortening of the long-chain hydrocarbon bonds in the polymeric structure. Likewise, Gaikwad et al [ 77 ] acknowledged that recycled ABS has less than 90% of the strength of virgin ABS.…”
Section: Systematic Review and Analysissupporting
confidence: 91%
“…Like [ 68 ], the authors of [ 71 , 72 ] found that internal defects are common in recycled polymers exposed to either extreme temperatures or UV light. Both [ 71 ] and Nagengast et al [ 84 ] agree that the internal defects in recycled polymers render them functionally unreliable, and, therefore, they are disposed of as waste. These defects imply a limitation on using 3D printing as a plastic recycling method.…”
Section: Systematic Review and Analysismentioning
confidence: 99%
See 3 more Smart Citations